Mechanical performance of concrete made of steel fibers from tire waste - Samarakoon, S. M. Samindi M. K. (2020)
Currently, the disposal of used tires is a worldwide challenge, due to their non-degradability. Therefore, recycling has become a potential solution for managing such waste. During recycling, materials such as rubber and steel are recovered from the used tires. The use of steel fibres, recovered from tire waste, as a raw material to reinforce concrete is an environmentally friendly and economically viable solution to manage the end-products of tire recycling. Few studies have been carried out to study the behaviour of fibre-reinforced concrete made using steel fibres recovered from tire waste. However, it has been found that there is the potential to reuse steel fibres recovered from tire waste (RF) as an alternative building material to manufactured steel fibres (SF). Nevertheless, more research is needed to verify that the structural performance of recycled fibre reinforced concrete (RFRC) is similar to that of manufactured fibre reinforced concrete (SFRC). Therefore, this study focuses on the laboratory testing of the mechanical properties of RFRC and compares them with those of SFRC. Moreover, the flexural performance of reinforced concrete beams cast with RF and SF have been tested to compare their performance.